До біографії академіка М. Кащенка - Готра, Олена Броніславівна (Чорноморський літопис, 2011)
Розглянуто джерела про життя, науково-організаційну, громадську та педагогічну діяльність академіка М. Кащенка. Відмічено, що найбільший пласт інформації містить особовий фонд М. Кащенка в Інституті архівознавства Національної бібліотеки України ім. В. І. Вернадського (ф. 11), використано матеріали Державного архіву міста Києва. Досліджено цінну джерельну інформацію в Інституті рукопису НБУВ.

The article analyses the sources which describe life, scientific-organizational, social and pedagogical activities of academician M. Kashchenko. It was noted that private Kashchenko’s fund at the Institute of Archival Science of the National Library of Ukraine named after V. I. Vernadsky contains a lot of information, and the materials of the Kyiv State Archive and the Institute of Manuscripts were also used.
Keywords: академик; личный фонд; биографические источники; научные труды; периодические издания; письма; academician; private fund; biographical sources; scientific papers; periodicals; letters